MANAJEMEN BUMDES MELALUI PERGULIRAN TERNAK SAPI DI DESA ARONGO KECAMATAN LANDONO KABUPATEN KONAWE SELATAN - Tonasa, Muhamad; Dewi , Andika (Jurnal Kewirausahaan Bukit Pengharapan, 2024)
The aim of this research is to describe the business products and services developed by BUMDes in Arongo Village, the factors inhibiting BUMDes in Arongo Village and the efforts made by the village government to overcome the factors inhibiting BUMDes Mepokoaso in Arongo Village, Landono subdistrict, South Konawe Regency. The type of research used is qualitative descriptive research with data collection methods in the form of observation, interviews, and documentation. The time series for this research was carried out from March 2024 to April 2024. The results of this research, firstly, are the business products and services developed by BUMDes Mepokoaso in Arongo Village, namely the rotation business of developing cattle livestock within the community in groups. The two factors inhibiting BUMDes Mepokoaso in Arongo Village are budget allocation factors, human resource factors, time factors, and threats. The third effort made by the Arongo Village Government, Landoono District, South Konawe Regency to overcome the inhibiting factors of BUMDes Mepokoaso is through participation and outreach. This research recommends references and considerations for overcoming factors inhibiting the growth and development of Village-Owned Enterprises (BUMDes).